2021
DOI: 10.21608/ejar.2021.56575.1070
|View full text |Cite
|
Sign up to set email alerts
|

Partial resistance to powdery mildew and leaf rust of wheat in Egyptian and CIMMYT genotypes

Abstract: Powdery mildew caused by Blumeria graminis f. sp. tritici and leaf rust caused by Puccinia triticina are among the most important widespread diseases of wheat (Triticum spp.). Seedling and adult plant partial resistance were assessed for both diseases in 46 wheat genotypes, including 20 Egyptian cultivars and 26 CIMMYT genotypes, during two growing seasons (2018/19 and 2019/20) in Egypt. Four Egyptian cultivars (cvs), Misr-1, Misr-2, Misr-3, Giza-171 and eight CIMMYT genotypes, Jupateco-73-R, Pavon-F-76, Opata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…with ITs of 0 and 2, respectively. The presence of Lr46 gene in the Sakha-94 Egyptian wheat cultivar was reported previously ( Draz and Abd El-Kreem, 2021 ). However, due to the highly susceptible reaction of this genotype in Exp.S.I.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…with ITs of 0 and 2, respectively. The presence of Lr46 gene in the Sakha-94 Egyptian wheat cultivar was reported previously ( Draz and Abd El-Kreem, 2021 ). However, due to the highly susceptible reaction of this genotype in Exp.S.I.…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, these genes were not included in the near isogenic lines evaluation due to seed lack. However, no previous studies postulated the presence of any of these genes in the Egyptian wheat germplasm ( Draz et al, 2015 , 2021 ; Atia et al, 2021 ; Draz and Abd El-Kreem, 2021 ). Furthermore, non of the 15 identified effective genes was mapped on this chromosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIL Pm2, NIL Pm3b and H 56771 with IT= '1' were highly resistant whereas, genotypes NIL Pm3c, CITR 15888 (Pm3f), Soissons (Pm3g), Wembley (Pm12), NC96BGTA5 (Pm 25), IWP 94 (Lr 23), TD 1, TD 4, TD 5, TD 6, TD 8, TD 12, TD 19, TD 20, UP 2382 and CMH 77.308 showing IT= '2' were moderately resistant. As has been observed in the present studies, seedling resistance to PM was reported in four Egyptian cultivars (Draz and El-Kreem 2021) and eight CIMMYT and 6 wheat 'Alcedo'-Ae. markgrafii chromosome disomic addition lines (Niu et al 2018), Indian advanced wheat breeding material (Basandrai et al 2016;Sood et al 2020).…”
Section: Testing Of Materials At Seedling and Adult Plant Stagessupporting
confidence: 88%
“…Favorable climatic conditions include different variables i.e. temperature, relative humidity(RH), and rain precipitation, which leads to an increasing threat of the disease (El Jarroudi et al, 2017;Bita and Farhad, 2019;Draz and Abd El-Kreem, 2021). The duration of the favorable temperature and moisture during wheat growth plays an important role in increasing yellow rust epidemics (van den Berg and van den Bosch, 2007).…”
Section: Introductionmentioning
confidence: 99%